Description of the Protective Feature of Oregano Essential Oil Sold as a Commercial Site on Rainbow Trout - Kuzgun, Nermin Karaton; Kırbag, Sevda (My University, 2020)
The essential oil extracted from plants has a shelf-life effect. This study was carried out to determine the difference of natural oregano essential oil, which is considered to be a potential food additive, from commercially available, and its effects on rainbow trout containment by using low amounts of this essential oil. The changes in rainbow trout samples were analyzed by applying commercially available oregano essential oil at a low rate (RT1: 1% and RT2: 2%), by looking at the following parameters. When the microbial load, sensory properties, pH, TVB, TBA numbers are examined in terms of thyme essential oil application and day relationship, the limit to be consumed in samples with 1% oregano essential oil is (RT1), on average, between the 3rd and the 6th days. It is between the 3rd and 9th days in the samples applied with 2% oregano essential oil (RT2). According to the microbial load results, the rainbow trout sample (RT: control) exceeded the consumable limit on day 6 th and showed the highest value (P <0.05). In addition, it has been proven with the TVB and TBA values that the samples applied with essential oil are of good quality. In a sense, the shelf life is stabilized thanks to the oregano essential oil. The preservative effect was greater as soon as the oregano essential oil concentration was greate.
Keywords: Rainbow trout; Commercial oregano essential oil